Difficulties in using correct English prepositions among EFL students - Abdalla, Ibrahim (JEES (Journal of English Educators Society), 2021)
The objectives of this study are to find out the reasons of the problem related to using correct English prepositions and find some solutions. The participants were ten students at levels seven and eight, at the Faculty of Sciences and Arts. The researcher used the Descriptive Statistical Method and collected the data via a written test as the main research tool. The data were then analyzed quantitaively. The results were as follows: Saudi students faced problems with using the correct prepositions after certain verbs. Students encountered difficulties in identifying the correct prepositional phrase. Students experienced the same problem with the use of English prepositions in writing tasks and in daily communication. The recommendations of this study are that students need to revise the use of English prepositions in general and need more practice in the use of prepositions after certain verbs. They also need to make a greater effort to use English prepositional phrases in their written work. Regarding writing courses, students need to focus more on the use of prepositions in general. Curriculum designers need more attention about teaching prepositions in their textbooks and curriculums. HIGHLIGHTS: Saudi students faced problems by using the correct prepositions after certain verbs. Students encountered difficulties in identifying the correct prepositional phrase. Students experienced the same problem with the use of English prepositions in writing tasks and in daily communication.